Employment in Europe 1997 : analysis of key issues. (Employment & social affairs. Employment & European social fund, 1998)
This publication is the second in an annual series of special Bulletins published in conjunction with the Employment in Europe report. It aims at analysing selected labour market issues in somewhat greater detail than is usually in the Report. The present Bulletin contains the following three studies: Employment-intensity in the EU.- Job turnover in the EU.- International and regional migration of working-age population in the EU.